Evaluation of Hematology Profiles and Measurement of Serum Cardiac Troponin Level in Canine Monocytic Ehrlichiosis - Osathanon, Rungrote; Moonarmart, Walasinee; Suksantilap, Naiyana; Krajangpit, Nattiya; Lekcharoensook, Piyanart; Julapanthong, Pruksa; Wongrerkngam, Nutthakulporn (The Thai Journal of Veterinary Medicine, 2013)
Canine monocytic ehrlichiosis (CME) is an important multisystemic disease in dogs which is caused by Ehrlichia canis (E. canis). Systemic inflammatory response syndrome (SIRS) and severe anemia from E. canis might be the potential causes of myocardial damage. Cardiac troponin T (cTnT) is considered to be a sensitive and specific biomarker for myocardial damage in many mammalian species. The objectives of this study were to evaluate the effect of CME on serum cTnT levels in dogs and to determine the relationship between serum cTnT and values obtained from hematology. Fifty-two client-owned dogs were recruited into this study and clinical data were thoroughly recorded. Blood samples were collected from 52 dogs and tested for antigen of E. canis by multiplex PCR. The cTnT levels were measured by Elecsys®/cobas e™ cTnT fourth-generation assay. The dogs were divided into 4 groups. The control group consisted of 15 healthy dogs. The negative group included 20 dogs presented with at least 2 inclusion criteria but yielded negative results for Multiplex PCR. The E. canis infected group consisted of 10 dogs, which were positive for E. canis only. Lastly, the other blood parasite infected group included 7 dogs with multiplex PCR positive for Babesia spp. and/or Hepatozoon canis. Results showed that serum cTnT concentration was not different among the 4 groups (p = 0.70) and did not significantly increase in dogs with natural E. canis infection. However, there was a negative correlation between cTnT and RBC, and a correlation of cTnT with age. These implied that anemia and aging might cause myocardial injury, consequently, increased serum cTnT level in both normal and E. canis infected dogs.